Answer: 7
Step-by-step explanation:
f(x) 3x+1
f(2) = 3(2) +1
f(2) = 6+1
= 7
Answer:
n=6
Step-by-step explanation:
4n + 1= 25
Move constant to the right
4n=25-1
Calculate
4n=25-1
Then divide on both sides
Answer:y - y1 = m(x + x1)
m = (y2 - y1)/(x2 - x1) = (-6 - 2)/(-1 - 5) = -8/(-6) = 4/3
y - 2 = 4/3(x - 5) is a possible answer
y + 6 = 4/3(x + 1) is also a possible answer
Step-by-step explanation:
can i be brainliest
Answer:
b/a
Step-by-step explanation:
Given,(b^-2)/a*(b^-3)
or,(b^-2+3)/a
or,b/a
Answer:
ok, y exactamente qué es eso?
en Colombia no sabemos que es eso
me darías coronita please
es para subir de rango